Biochemical characterization of microbial type terpene synthases in two closely related species of hornworts, Anthoceros punctatus and Anthoceros agrestis. (May 2018) - Xiong, Wangdan; Fu, Jianyu; Köllner, Tobias G.; Chen, Xinlu; Jia, Qidong; Guo, Haobo; Qian, Ping; Guo, Hong; Wu, Guojiang; Chen, Feng
Abstract: Microbial terpene synthase-like ( MTPSL ) genes are a type of terpene synthase genes only recently identified in plants. In contrast to typical plant terpene synthase genes, which are ubiquitous in land plants, MTPSL genes appear to occur only in nonseed plants. Our knowledge of catalytic functions of MTPSLs is very limited. Here we report biochemical characterization of the enzymes encoded by MTPSL genes from two closely related species of hornworts, Anthoceros punctatus and Anthoceros agrestis . Seven full-length MTPSL genes were identified in A. punctatus ( ApMTPSL1 - 7 ) based on the analysis of its genome sequence. Using homology-based cloning, the apparent orthologs for six of the ApMTPSL genes, except ApMTPSL2, were cloned from A. agrestis . They were designated AaMTPSL1, 3–7 . The coding sequences for each of the 13 Anthoceros MTPSL genes were cloned into a protein expression vector. Escherichia coli -expressed recombinant MTPSLs from hornworts were assayed for terpene synthase activities. Six ApMTPSLs and five AaMTPSLs, except for ApMTPSL5 and AaMTPSL5, showed catalytic activities with one or more isoprenyl diphosphate substrates. All functional MTPSLs exhibited sesquiterpene synthase activities. In contrast, only ApMTPSL7 and AaMTPSL7 showed monoterpene synthase activity and only ApMTPSL2, ApMTPSL6 and AaMTPSL6 showed diterpene synthase activity. Most MTPSLs from Anthoceros contain uncanonical aspartate-rich motif in the form of either 'DDxxxD' or 'DDxxx'. Homology-based structural modeling analysis of ApMTPSL1 and ApMTPSL7, which contain 'DDxxxD' and 'DDxxx' motif, respectively, showed that 'DDxxxD' and 'DDxxx' motifs are localized in the similar positions as the canonical 'DDxxD' motif in known terpene synthases. To further understand the role of individual aspartate residues in the motifs, ApMTPSL1 and ApMTPSL7 were selected as two representatives for site-directed mutagenesis studies. No activities were detected when any of the conserved aspartic acid was mutated into alanine. This study provides new information about the catalytic functions of MTPSLs and the functionality of their uncanonical aspartate-rich motifs, and builds a knowledge base for studying the biological importance of MTPSL genes and their terpene products in nonseed plants. Graphical abstract: The hornworts Anthoceros punctatus and Anthoceros agrestis each contains a small family of microbial-terpene synthase like ( MTPSL ) genes. Recombinant proteins expressed in E. coli from most Anthoceros MTPSL genes showed sesquiterpene synthase activities, converting farnesyl diphosphate to a few to nearly 20 sesquiterpenes.Image 1 Highlights: Hornworts Anthocerus punctatus and Anthocerus agrestis contain MTPSL genes. Most Anthocerus MTPSL genes encode active terpene synthases. The uncanonical aspartate-rich motifs in MTPSLs are important for catalysis.